1998
DOI: 10.1177/0891243298012003004
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Male Work Environments and Organizational Policies on Women's Experiences of Sexual Harassment

Abstract: Women's experiences with sexual harassment were analyzed with three types of variables: occupational and workplace sex ratios, organizational policies and procedures for dealing with sexual harassment problems, and women's cultural status (age and marital status). Regression analyses revealed that extent of contact with men was a key predictor of incidence of harassment, number of different types of harrassment, sexual comments, sexual categorical remarks, and sexual materials. Gender predominance was a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
184
0
6

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(198 citation statements)
references
References 29 publications
8
184
0
6
Order By: Relevance
“…The contact hypothesis suggests that harassment increases with exposure to men (Gruber 1998;Gutek, Cohen, and Konrad 1990;KauppinenToropainen and Gruber 1993), and that the percentage of men in the workplace increases the incidence of harassment (De Coster, Estes, and Mueller 1999). If harassment itself elicits antiharassment measures, then the percentage of men should increase the use of sexual harassment procedures and training, and the percentage of nonminorities should increase the use of general harassment procedures that cover racial harassment.…”
Section: Organizational Demography and The Risk Of Harassmentmentioning
confidence: 99%
“…The contact hypothesis suggests that harassment increases with exposure to men (Gruber 1998;Gutek, Cohen, and Konrad 1990;KauppinenToropainen and Gruber 1993), and that the percentage of men in the workplace increases the incidence of harassment (De Coster, Estes, and Mueller 1999). If harassment itself elicits antiharassment measures, then the percentage of men should increase the use of sexual harassment procedures and training, and the percentage of nonminorities should increase the use of general harassment procedures that cover racial harassment.…”
Section: Organizational Demography and The Risk Of Harassmentmentioning
confidence: 99%
“…Furthermore, studies have found that individuals with low organizational status, especially within male-dominated organizations, are more likely to experience sexual harassment (e.g., Buchanan, Settles, & Woods, 2008;Firestone & Harris, 1999;Fitzgerald et al, 1999;Gruber, 1998Gruber, , 2003 and individuals with higher organizational status are less likely to be targets of sexual harassment (Cortina, Magley, Williams, & Langhout, 2001;Settles, Buchanan, & Colar, 2012). In addition, when the perpetrator has higher status and power, individuals perceive their sexual harassment as being more severe (e.g., Cortina, Fitzgerald, & Drasgow, 2002;O'Connell & Korabik, 2000).…”
Section: Sexual Harassment Appraisalsmentioning
confidence: 99%
“…Considering sexual harassment lawsuits can cost companies tens of thousands to millions of dollars per case (EEOC, 2006), many organizations have taken the EEOC's advice to heart. Empirical findings are mixed, however, as to whether having a policy is enough to deter incidents of sexual harassment in and of itself (Bergman, Langhout, Palmieri, Cortina, & Fitzgerald, 2002;Bond, 1995;Gruber, 1998;Pierce, Rosen, & Hiller, 1997;Reese & Lindenberg, 2004). As behavior analysts are well aware, "behavior is a function of interactions between a person and that person's environment" (Brethower, 2002).…”
mentioning
confidence: 99%
“…One of the most prominent characteristics researched to date is the sex ratio of the occupation and/or work place (DeCoster, Estes, & Mueller, 1999;Fitzgerald, Drasgow, Hulin, Gelfand, & Magley, 1997;Gruber, 1998;Mueller, DeCoster, & Estes, 2001;O'Hare & O'Donohue, 1998). In fact, feminist theory suggests a core objective of sexual harassment has been to illustrate to women that they are not wanted in certain workplaces and that they are not respected as members of particular work groups (O'Hare & O'Donohue, 1998;Reskin & Padavic 1994).…”
mentioning
confidence: 99%
See 1 more Smart Citation